2006
DOI: 10.1080/14734220600724569
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Purkinje neurones and Bergmann glia

Abstract: Throughout the development of the cerebellar cortex, Purkinje neurones interact closely with Bergmann glial cells, a specialized form of astrocyte. This review summarizes the intimate developmental, anatomical and functional relationships between these two cell types, with particular emphasis on recent discoveries regarding glutamate release from climbing and parallel fibres as a pathway for signalling synaptic activity to Bergmann glia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 106 publications
5
95
1
1
Order By: Relevance
“…Moreover, cerebellar Purkinje cells are inhibitory neurons that do not express adenosine A1 receptors (1,23). It is, however, of interest that both studies concluded that glia Ca 2+ signaling triggers an increase in up states and may reflect that glia use different strategies to modulate neural circuits depending on their location in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cerebellar Purkinje cells are inhibitory neurons that do not express adenosine A1 receptors (1,23). It is, however, of interest that both studies concluded that glia Ca 2+ signaling triggers an increase in up states and may reflect that glia use different strategies to modulate neural circuits depending on their location in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellar PC is a unique neuron due to its huge soma and dendritic tree, its enormous number of synapses and its high vulnerability to pathologic conditions Sarna and Hawkes, 2003). So far, there is good evidence that glial cells influence the function of synaptic inputs to PCs (Bellamy, 2006;Bordey and Sontheimer, 2003;Brockhaus and Deitmer, 2002;Marcaggi et al, 2003;Takayasu et al, 2005), but it is unclear, whether they also contribute to their development. To address this issue, we established immunopanning protocols to enrich for PCs from postnatal mice and to culture them under glia-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Bergmann glial cell is a specialized astrocyte of the cerebellar cortex, which has a close anatomical and functional association with Purkinje and granule neurons throughout development (Bellamy, 2006;Muller and Kettenmann, 1995;Yamada and Watanabe, 2002). In the adult cerebellum, Bergmann glia display complex lateral processes, which sprout from the radial fibers first described by Bergmann, to form ''microdomains'' that enwrap the numerous synapses of the molecular layer (Grosche et al, 1999(Grosche et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%